Exploring the prophylactic role of soy isoflavones against polycystic ovarian syndrome. Issue 9 (9th July 2021) - Manzar, Nishaf; khan, Safwan Ahmad; Fatima, Najum; Nisa, Mehr un; Ahmad, Muhammad Haseeb; Afzal, Muhammad Inam; Saeed, Hafiz Fahad Ullah; Imran, Muhammad; Anjum, Faqir Muhammad; Arshad, Muhammad Sajid
Abstract: Soy isoflavones (SI) have strong estrogenic effect in tissues by binding to estrogen receptors and might be beneficial for women with polycystic ovarian syndrome (PCOS) by reduction in testosterone, cholesterol, insulin, weight gain, inflammatory markers, and oxidative stress. The study was planned to examine the effect of various levels of SI on nutrient intake, digestibility, lipid profile, insulin, and reproductive hormones of estradiol valerate (4 mg/rat/IM) PCOS induced rat models. Thirty‐six Wistar 45 days old rats weighing 95 ± 5 g were divided into 4 groups, each having 9 rats: C (control: without SF), SF10 (SF 0.10 g/kg BW), SF15 (SF 0.15 g/kg BW), and SF20 (SF 0.20 g/kg BW). SF was given through the oral gavage. Food and water were offered ad libitum, and intake was recorded daily. During last week of trial, collected feces by total collection method and blood samples were used to calculate nutrient digestibility and biochemical analysis, respectively. Estrogen, progesterone, and prolactin were ( p  < .05) high in rats fed SF diet that was 4% and 30% increase from C, respectively. Insulin, testosterone, FSH, and LH were lowest in rats fed diet SF20. Significant ( p  < .05) reduction in cholesterol was observed in rats fed SF15 and SF20 as compared to C. Serum HDL was improved ( p  < .05) in all SIF0.10, SIF0.15, and SIF0.20 in comparison with PC. Serum LDL was significantly reduced to 68.89 ± 4.36 (mg/dl) in SIF0.20 and to 108.20 ± 4.14 (mg/dl) in SIF0.15, whereas insignificant reduction was observed in SIF0.10 as compared to PC. Highly significant reduction was noted in triglycerides level in SIF0.20; however, significant reduction was observed in both SIF0.10 and SIF0.15 as compared to PC after 3 months of treatment with soy isoflavones. Abstract : The objective of this study was to investigate the effect of different levels of soy isoflavones on blood insulin, lipid, and reproductive hormones profile of the female rats with PCOS.